Complex Realism, Applied Social Science and Postdisciplinarity: A Critical Assessment of the Work of David Byrne. Issue 5 (24th October 2014) - Holland, Dominic
Abstract : In this review essay I offer a critical assessment of the work of David Byrne, an applied social scientist who is one of the leading advocates of the use of complexity theory in the social sciences and who has drawn on the principles of critical realism in developing an ontological position of 'complex realism'. The key arguments of his latest book, Applying Social Science: The Role of Social Research in Politics, Policy and Practice constitute the frame of the review; however, since these overlap with those of his previous books, Interpreting Quantitative Data and Complexity Theory and the Social Sciences, I consider all three books together. I identify aspects of Byrne's ontological position that are in tune with the principles of original and dialectical critical realism and aspects that are not. I argue that these inconsistencies, which Byrne must resolve if he is to take his understanding of complexity further, stem from the residual influence of various forms of irrealism in his thinking.